Predictors of adherence to the Mediterranean diet from the first to the second trimester of pregnancy - Abreu, Sandra (2015)
Background: Although changes in eating patterns may occur during gestation, predictors of these changes have not been explored. This study aimed to identify predictors of adherence to the Mediterranean diet (MD) from the first to second trimester of pregnancy. Methods: A prospective study was conducted with 102 pregnant women aged 18-40, from the city of Porto, Portugal. Socio-demographic and lifestyle characteristics were assessed through a questionnaire. Food consumption was assessed with a three-day food diary completed during the first and second trimesters. Participants were categorized according to their change in adherence to the MD into the negative change group (i.e., women who had low adherence in each trimester or had high adherence in the first trimester and then low adherence in the second) and the positive change group (i.e., women who had high adherence in both trimesters or had low adherence in the first trimester and then high adherence in the second). Conditional stepwise logistic regression models were performed to assess the potential predictors of negative MD change. Results: Among the 102 women, 39.2% had negative change from the first to the second trimester. The logistic model's results show that being married (OR=0.26, 95%CI: 0.10,0.76) and having a higher intake of vegetables in the first trimester (OR=0.17, 95%CI: 0.10, 0.43) were associated with lower odds of having a negative change in adherence to the MD from the first to second trimester. Conclusion: Marital status and vegetable consumption seem to be associated with a lower occurrence of negative change in adherence to the MD from early to middle pregnancy.